2015
DOI: 10.1103/physreve.92.062408
|View full text |Cite
|
Sign up to set email alerts
|

Simple models of the hydrofracture process

Abstract: Hydrofracturing to recover natural gas and oil relies on the creation of a fracture network with pressurized water. We analyze the creation of the network in two ways. First, we assemble a collection of analytical estimates for pressure-driven crack motion in simple geometries, including crack speed as a function of length, energy dissipated by fluid viscosity and used to break rock, and the conditions under which a second crack will initiate while a first is running. We develop a pseudo-three-dimensional nume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…Surface area of same order was reported by Johri and Zoback [63] based on field fracture data and mechanical modeling. Marder et al [56] presented an analytical solution of fracture generation and simulated 2000 wells to show that the typical spacing between the large fracture planes should be 1-4 m to maintain production in mudrock. They argued that physically such a small fracture spacing may be impossible, but this distance can be considered as characteristic distance for the branching, complex fracture network.…”
Section: Constraints On Srv Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…Surface area of same order was reported by Johri and Zoback [63] based on field fracture data and mechanical modeling. Marder et al [56] presented an analytical solution of fracture generation and simulated 2000 wells to show that the typical spacing between the large fracture planes should be 1-4 m to maintain production in mudrock. They argued that physically such a small fracture spacing may be impossible, but this distance can be considered as characteristic distance for the branching, complex fracture network.…”
Section: Constraints On Srv Parametersmentioning
confidence: 99%
“…The hydrofracture permeability is infinite relative to the stimulated matrix. Adapted from [56]. (b) Planar view of half-SRV after hydrofracturing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This low permeability results from the small cross-sections of pore throats and the scaledependent connectivity that ranges from strong at nanoscale to increasingly sparser at micro and higher scales. Patzek et al (2013) and Marder et al (2015) showed that methane in shales is produced through the highways of loosely connected micropores and multiscale cracks, man-made and natural, into which a background continuum of the tiny nanopores feeds gas. This background continuum with the ordered, densely packed methane molecules can masquerade at times as the BET-like, multi-layer methane adsorption, Yu et al (2016).…”
Section: Introductionmentioning
confidence: 99%
“…3. The fractured gas-bearing mudrock formations (shales) are the essentially multiscale, Nelson (2009), and multiphysics systems, Marder et al (2015), and their behavior is complex. Yet, we try to replace shale complexity with a set of slim cylindrical capillaries that flow methane with slip at the capillary walls.…”
Section: Introductionmentioning
confidence: 99%